Hubungan Antara Pengetahuan Ibu Dan Dukungan Suami Dengan Pemberian Asi Eksklusif Di Puskesmas Baki Kabupaten Sukoharjo - ISMAN, NOVIC, Bejo Raharjo, SKM, M.Kes, Anisa Catur Wijayanti, SKM., M.Epid (2015)
Exclusive breastfeeding is breastfeeding without given any additional food until the baby is 6 months old. The purpose of this study was to analyze the relationship between mother's knowledge and husband support with exclusive breastfeeding in Puskesmas Baki Sukoharjo. The type of this research use the analytic survey with cross sectional approach. The population in this study was mothers with children aged 6-24 months. The sample in this study as many as 140. Random Sampling technique with the method of Systematic Random Sampling technique while using Chi Square test. Mothers who have less knowledge about exclusive breastfeeding as much as 46.4% and 56.4% as much as husbands support exclusive breastfeeding. Results of this study indicate that there is a relationship between mother knowledge (p = 0.024 : RP = 1.484 : 95% CI = 1.109 to 1.985) and there was no relationship between husband support (p = 0.460) with exclusive breastfeeding in Puskesmas Baki Sukoharjo.